If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -20.8 = 1 + 1.2 Reorder the terms: -20.8 + 2a = 1 + 1.2 Combine like terms: 1 + 1.2 = 2.2 -20.8 + 2a = 2.2 Solving -20.8 + 2a = 2.2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '20.8' to each side of the equation. -20.8 + 20.8 + 2a = 2.2 + 20.8 Combine like terms: -20.8 + 20.8 = 0.0 0.0 + 2a = 2.2 + 20.8 2a = 2.2 + 20.8 Combine like terms: 2.2 + 20.8 = 23 2a = 23 Divide each side by '2'. a = 11.5 Simplifying a = 11.5
| 7x-2=343 | | M(x)=-x^2-6x-5 | | x(4-3m)+1=x(3-4m)-m^2 | | 1/x+1/2=5/6 | | 1/x+1/2 | | y=5/3x+25/3-9 | | 3/2+4 | | y+9=5/3x+25/3 | | 3/2b+4b | | P(x)=60x-x^2 | | F(x)=30+x-x^2 | | x(x-2)=(x+2)2 | | 10x^2+15=-31x | | 3/2+4b+45-90+90=540 | | -(4-4x)-7x=-5(x+6) | | -2x^2+9x-7=0 | | 3/2+(b+45)+(2b-90)+90+b=540 | | 10a+2=15 | | 9+3=12 | | 12+2(-3x-7)=5x-4 | | 3c+8=4(c-2)+7 | | -2x-6=11 | | -8x-4=14 | | -9+9=5/3(-5+5) | | -2(2x-3)-5=9(x-2) | | y+9=5/3(-5+5) | | 2(x-3)=6-3(x-2) | | 51a-56=44a+-51a | | 3x-37=2x+17 | | c^2-2c-24=0 | | n^2-10n=-2 | | 20-8Q=Q^2 |